PENGARUH PERTUMBUHAN EKONOMI, PENDAPATAN ASLI DAERAH (PAD), DANA ALOKASI UMUM (DAU), DANA ALOKASI KHUSUS (DAK) TERHADAP BELANJA MODAL DI KABUPATEN KOTA PROVINSI JAWA TENGAH (PERIODE 2014-2016) - Nur Aliyah, 15.05.52.0309; Maryono, Maryono (Students' Journal of Accounting and Banking, 2019)
The purpose of this study was to analyze whether economic growth as measured by the value of gross regional domestic product (GDP), Pedapatam Asli Daerah, General Allocation Funds, and Special Allocation Funds had an effect on capital expenditure in kabuapaten / cities in Central Java province. The dependent variable in this study is Capital Expenditures while for the independent variables are Economic Growth, Local Revenue, General Allocation Funds and Special Allocation Funds. The population in this study were districts / cities in Central Java in 2014-2016. The sample used in this study is as many as 35 districts / cities in Central Java sourced from the 2014-2016 Budget APBD Realization Report. The testing technique used is multiple regression analysis. The results of this study indicate that Economic Growth has no significant effect on Capital Expenditures, Regional Original Income has a significant positive effect on Capital Expenditures, General Allocation Funds have a significant positive effect on Capital Expenditures, Special Allocation Funds have a significant positive effect on Capital Expenditures. Keywords: Economic Growth, Local Revenue, General Allocation Funds, Special Allocation Funds.